Influência dos impactos por supressão vegetal na diversidade beta de mamíferos em áreas dos biomas Cerrado-Amazônia - Amorim, Rooney Pinheiro de (2021)
The impact of vegetation suppression is an important factor influencing the variation of the beta diversity of terrestrial fauna, which can be partitioned into replacement or nesting components, when communities in impacted areas become subsets of the richest places. In the analyses, the effect of large-scale spatial heterogeneity should be considered, which generally influences the predominance of the replacement component, while at different scales, nesting has an increased influence, especially in environments with a history of deforestation. The purpose of study was to investigate the variation of beta diversity by impacts of plant suppression on a wide scale (interbiomic) and at separate scales of the Cerrado and Amazon Biomes (intrabiomic). Based on inventories of medium and large mammals, the sørensen index was calculated, divided into replacement and nesting components and, using a restricted ordination method (CAP), the influence of spatial variables and plant suppression of the sample areas (impacted/non-impacted), as well as other predictor variables of interest. On the interbiomic scale, the beta diversity by substitution showed a higher percentage, with a significant effect of the spatial variable on this component. In nesting, however, there was a predominance of the significant effect of suppression impacts. Regarding the scale of the Amazon Biome, there was a reduction in the influence of spatial variation on the replacement component and a significant influence of the impacts by suppression both in the nesting component and in the replacement component. In the Cerrado Biome, there was also a reduction in the effect of spatial variation on replacement, but in nesting, the significant effect was entirely related to the variable of plant suppression impacts. The results of this study show, therefore, that the effects of plant suppression on the beta diversity of medium and large mammals were not dependent on the variation of the scales of analysis, but on other factors related to this study. The progress of the effects of vegetation suppression was also demonstrated, highlighting the urgent need to prioritize the conservation of native vegetation remnants where they exist, to minimize the impacts, in addition to actively restoring already degraded areas.